Keistimewaan Manusia (Analisis Pesan Dakwah Felix Siauw dalam Video Youtube Kajian Islam Rahmatan Lil Alamin) - Azami, Hadiana Trendi (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Abstract This article will discuss the idiosyncrasy of humans by using a qualitative method and descriptive analysis approach. According to Felix Siauw in understanding the potential of human life should be dissected in advance about human nature and the factors that influence it. After that can be aware of potential human life that is at once a privilege of the human. Among the privileges of man, namely physical needs, instincts, sense and mind, and nature for days. The purpose of this Article review about understanding the verses of the Qur'an and the message of da'wah put forward by Felix Siauw in channel Youtube Felix Siauw. How Felix Siauw in explaining the nature of privileges human. How faceted shape of the idiosyncrasy of man according to Felix Siauw, functionality, and usability to determine the potential of human life in the context of the present. The study will be reviewed from the perspective of maqasid of shari'ah especially related to the message verses of the Qur'an. Keywords: Idiosyncrasy, Human, Potential, Life. Abstrak Artikel ini akan membahas keistimewaan manusia dengan menggunakan metode kualitatif dan pendekatan analisis deskriptif. Menurut Felix Siauw dalam memahami potensi kehidupan manusia harus dibedah terlebih dahulu tentang hakikat manusia dan faktor-faktor yang mempengaruhinya. Setelah itu, dapat diketahui potensi kehidupan manusia yang sekaligus menjadi keistimewaan manusia. Diantara keistimewaan manusia yaitu kebutuhan jasmani, naluri, akal dan pikiran, dan fitrah untuk bertauhid. Tujuan Artikel ini mengkaji tentang pemahaman ayat al-Qur’an dan pesan dakwah yang dikemukakan oleh Felix Siauw dalam chanel Youtube Felix Siauw. Bagaimana cara Felix Siauw dalam menjelaskan hakikat keistemewaan manusia. Bagaiamana ragam bentuk keistimewaan manuia menurut Felix Siauw, fungsi dan kegunaan untuk mengetahui potensi kehidupan manusia dalam konteks kekinian.Kajian tersebut akan dikaji dalam perspektif maqasid syari’ah terutama terkait pesan ayat al-Qur’an. Kata kunci : Keistimewaan, Manusia, Potensi, Hidup.